If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + 6)(n + -6) = 5n Reorder the terms: (6 + n)(n + -6) = 5n Reorder the terms: (6 + n)(-6 + n) = 5n Multiply (6 + n) * (-6 + n) (6(-6 + n) + n(-6 + n)) = 5n ((-6 * 6 + n * 6) + n(-6 + n)) = 5n ((-36 + 6n) + n(-6 + n)) = 5n (-36 + 6n + (-6 * n + n * n)) = 5n (-36 + 6n + (-6n + n2)) = 5n Combine like terms: 6n + -6n = 0 (-36 + 0 + n2) = 5n (-36 + n2) = 5n Solving -36 + n2 = 5n Solving for variable 'n'. Reorder the terms: -36 + -5n + n2 = 5n + -5n Combine like terms: 5n + -5n = 0 -36 + -5n + n2 = 0 Factor a trinomial. (-4 + -1n)(9 + -1n) = 0Subproblem 1
Set the factor '(-4 + -1n)' equal to zero and attempt to solve: Simplifying -4 + -1n = 0 Solving -4 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1n = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1n = 0 + 4 -1n = 0 + 4 Combine like terms: 0 + 4 = 4 -1n = 4 Divide each side by '-1'. n = -4 Simplifying n = -4Subproblem 2
Set the factor '(9 + -1n)' equal to zero and attempt to solve: Simplifying 9 + -1n = 0 Solving 9 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1n = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1n = 0 + -9 -1n = 0 + -9 Combine like terms: 0 + -9 = -9 -1n = -9 Divide each side by '-1'. n = 9 Simplifying n = 9Solution
n = {-4, 9}
| 7+6x=5+3x | | -6=-5x+x^2 | | 11(v+4)-3v=4(2v+3)-17 | | 27d^6+8g^12=0 | | 3+2w=19 | | (x)=-2x^2+7x-4 | | 2lnx+4=5+lnx | | wx^2-w^2x^2=0 | | F(x)=5x^2+10x+12 | | 6t+8=26-3t | | 6y-1=8y-3y | | x/2=3-x/4 | | 8x^3-12x^2-10x+15= | | (x-1)/7-(x-3)/2=1 | | X=4x^2-9x+2 | | 4a+6=36 | | (x)=-2x^2+9x+5 | | x-.03x=158.92 | | 2g+6=6g-6 | | H(x)=-2x^2+9x+5 | | F(x)=4cos^2-6sin^2x | | x-3y=y+2x | | 4z-1=7z+4z | | (2x+16)=(4x-4) | | 3x^2+5=-3x+6 | | 7/8x-3/8=5/8 | | 6^-2=(1/36) | | x-y+2=x-2+y | | 70+x+30+2x-10=180 | | 11b+7=46 | | 6p-5=10p-25 | | x-6x=25 |